Diversity and dynamics of microbial communities during spontaneous fermentation of Cabernet Sauvignon (Vitis vinifera L.) from different regions of China and their relationship with the volatile components in the wine. (June 2022) - Wei, Ruteng; Ding, Yinting; Chen, Ning; Wang, Lin; Gao, Feifei; Zhang, Liang; Song, Rui; Liu, Yihui; Li, Hua; Wang, Hua
Graphical abstract: Highlights: Must microbiota and wine volatile components could differentiate wine estates. Fungi alpha diversity decreased during fermentation, while bacteria were inconsistent. The fungi diversity of final wine can correctly identify wine estates used in this study. The dominant microbial species largely determine the volatile composition of wine. Associations between fungal species and wine metabolites were elucidated. Abstract: Wine presents the most distinct geographic signatures among all agricultural products, and these geographic characteristics of the wine are enhanced by the actions of indigenous microorganisms. China is one of the largest wine-producing and consuming nations in the world. The wine-related microbial resources are abundant in China, although their geographic distribution patterns and their contribution to the aroma of wine remain to be elucidated. In the present study, Cabernet Sauvignon samples from four wine-producing regions in China were subjected to high-throughput sequencing and HS-SPME-GC-MS techniques to study the diversity and dynamics of the microorganisms that were present during the spontaneous fermentation process and to provide a preliminary understanding of the contribution of these microorganisms to the volatile components of the wine. The results revealed significant differences in the microbial diversity in the grape musts among different vineyards, which led to significant differences in the composition of the volatile metabolites of the produced wine. Moreover, while the fermentation process was observed to have reshaped the structure of the microbial community, specific characteristics of the vineyard were retained at the completion of the fermentation process. The associations between microbiota diversity and wine chemicals suggested that the dominant species during the fermentation process largely determined the volatile components of the wine. The present study enhances the understanding of Chinese wine terroir and provides a scientific basis for maintaining the regional microbial biodiversity to sustain viticulture and winemaking.